BryForTrait – A life‐history trait database of forest bryophytes. (5th July 2018) - Bernhardt‐Römermann, Markus; Poschlod, Peter; Hentschel, Jörn
Abstract: In ecological research, plant functional trait analyses are widely applied to understand to what extent the inter‐specific variation in trait attributes has an adaptive value or to predict ecosystem processes and changes. Compared to vascular plants, trait studies using bryophytes are scarce, which is likely due to missing trait information for bryophyte species. With the BryForTrait database, we want to reduce this deficit. Our database represents a compilation of autecological information and morphological and regenerative trait data on different stages of the life cycle of bryophytes occurring in forest ecosystems. The database contains information for 35 traits and 721 Central European bryophyte species; in total more than 23, 000 trait values. The BryForTrait database will enable future trait studies, providing new insights into bryophyte‐dominated ecosystems. Abstract : Bryophytes are an important part of the vegetation, but trait‐based analysis of their assemblages are limited because of missing trait information. With the BryForTrait database, we close this gap by providing autecological information, morphological and regenerative trait data on different stages of the life‐cycles for 721 Central European bryophyte species mainly occurring in forest ecosystems.